Incidence and predictors of left ventricular function change following ST-segment elevation myocardial infarction - Liu, Chuanfen; Guo, Meng; Cui, Yuxia; Wu, Manyan; Chen, Hong (Frontiers in Cardiovascular Medicine, 2023)
Aim: We sought to investigate the predictors of left ventricular ejection fraction (LVEF) change after ST-segment elevation myocardial infarction (STEMI). Methods: The study consecutively enrolled 312 patients with STEMI who underwent primary PCI between January 2015 and December 2016. We finally analyzed the LVEF change in 186 patients from baseline to follow-up. Logistic regression analysis was performed to evaluate multivariable predictors of LVEF improvement at follow-up. Results: The mean age of the patients was 61.3 ± 12.5 year, with 78.5% being male. The median duration of follow-up after STEMI was 1021 (389 - 1947) days. 54.3% had a decrease in LVEF and 45.7% experienced improvement in LVEF after primary PCI through a long-term follow-up. Lower peak troponin I, lower baseline LVEF, non-anterior MI and no previous myocardial infarction history were independent predictors of LVEF improvement from baseline to follow-up. Conclusion: More than half of patients with STEMI had a decrease in LVEF during long-term follow-up. LVEF recovery can be predicted by baseline characteristics.